Quality of written informed consent forms for electroconvulsive therapy in Australia: a comparative analysis. (April 2022) - Jagadheesan, Karuppiah; Walker, Frances; Lakra, Vinay
Objectives: We compared the quality of the written informed consent forms for electroconvulsive therapy (ECT) in Australian jurisdictions. Method: For this comparative audit-type study, a checklist was developed to compare informed consent forms from different jurisdictions. The main information sources for consent forms were government health department websites and Google. The directors of clinical services were contacted if a consent form was not available through a web source. Results: Majority of the informed consent forms covered information about ECT, general anaesthesia and alternative treatments, supports available for decision making, and a reference to the right to withdraw consent. Missing information affected information areas such as likely outcome if no ECT, lack of guaranteed response and cultural and linguistic supports. Conclusions: A standardised consent form that can be used across all jurisdictions can help improve the ECT practice.